Role of Management and Policy Issues in Computer Security: Rand Report R-609 within Organization - Boujmil, Jamal; Tagmouti, N.; Raissouni, N. (Transactions on Engineering and Computing Sciences, 2017)
The need to provide strengthened Security for Information Systems within organization increases day after day seeing the large development of interconnection of the World Wide Web and the clear effect that results by the frequent and multiple productions of attacks and threats. This feebleness and gap in current information technologies urge researcher to face by developing more secure systems of Sharing Resources. The history of securing Information Systems began with the concept of Computer Security in its Global meaning Physical and Non-Physical. Thus, by 1967 the Department of Defense of USA published the R-609 which is considered as the first step in the wide world of Information security including Securing the data, Limiting random and unauthorized access to that data and Involving personnel from multiple levels of the organization in information security. The purpose of this paper is to analyze and evaluate the role of management and policy issues in computer security that proposes Rand Report R-609 within organization.